Epilepsy and ADHD (International Journal of Medical and Surgical Sciences, 2021)
Epilepsy encompasses a set of heterogeneous seizure disorders, with various clinical characteristics that exclude a unique etiological mechanism. Individuals with this disease have a significantly higher rate for the development of psychiatric and neurological conditions. Children with epilepsy have two to three times increased risk of developing ADHD when compared to healthy individuals, while one in five epileptic adults have ADHD symptoms. In children with epilepsy, the severity and frequency of seizures and an earlier age at the onset of seizures are common risk factors for ADHD. A narrative review of the literature was carried out and articles published in the period between 2003 and 2021 in digital databases of the health area (LILACS, Medline, Web of Science, SciELO and PubMed) were selected. The review showed that epilepsy can increase the risk of developing ADHD in children, and that benign rolandic epilepsy is the most diagnosed type in these children, which even has a high rate of neurobehavioral disorders with associated ADHD symptoms. Early diagnosis and appropriate management lead to a better prognosis in this group of patients.
Keywords: Epilepsy; ADHD; children